(untitled) (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article analyzes Michael Walzer’s distinction between covering-law universalism and reiterative universalism as competing approaches to nationalism and moral pluralism. It argues that legitimate national communities should be grounded in cultural diversity, moral autonomy, and the recognition of the equal rights of other nations rather than in universal missions or historical determinism. The article emphasizes that reiterative universalism provides a more adequate framework for understanding national identity, democratic legitimacy, and peaceful coexistence in a pluralistic international order. This abstract is generated with artificial intelligence.